Effects of Fecal Sampling on Preanalytical and Analytical Phases in Quantitative Fecal Immunochemical Tests for Hemoglobin. Issue 3 (July 2017) - Rapi, Stefano; Berardi, Margherita; Cellai, Filippo; Ciattini, Samuele; Chelazzi, Laura; Ognibene, Agostino; Rubeca, Tiziana
Background: Information on preanalytical variability is mandatory to bring laboratories up to ISO 15189 requirements. Fecal sampling is greatly affected by lack of harmonization in laboratory medicine. The aims of this study were to obtain information on the devices used for fecal sampling and to explore the effect of different amounts of feces on the results from the fecal immunochemical test for hemoglobin (FIT-Hb). Methods: Four commercial sample collection devices for quantitative FIT-Hb measurements were investigated. The volume of interest (VOI) of the probes was measured from diameter and geometry. Quantitative measurements of the mass of feces were carried out by gravimetry. The effects of an increased amount of feces on the analytical environment were investigated measuring the Hb values with a single analytical method. Results: VOI was 8.22, 7.1 and 9.44 mm 3 for probes that collected a target of 10 mg of feces, and 3.08 mm 3 for one probe that targeted 2 mg of feces. The ratio between recovered and target amounts of devices ranged from 56% to 121%. Different changes in the measured Hb values were observed, in adding increasing amounts of feces in commercial buffers. Conclusions: The amounts of collected materials are related to the design of probes. Three out 4 manufacturers declare the same target amount using different sampling volumes and obtaining different amounts of collected materials. The introduction of a standard probes to reduce preanalytical variability could be an useful step for fecal test harmonization and to fulfill the ISO 15189 requirements.